Stimulation of in vivo dopamine transmission and intravenous self-administration in rats and mice by JWH-018, a Spice cannabinoid. (December 2015) - De Luca, M.A.; Bimpisidis, Z.; Melis, M.; Marti, M.; Caboni, P.; Valentini, V.; Margiani, G.; Pintori, N.; Polis, I.; Marsicano, G.; Parsons, L.H.; Di Chiara, G.
Abstract: The synthetic cannabinoid 1-pentyl-3-(1-naphthoyl)-indole (JWH-018) has been detected in about 140 samples of a smokable herbal mixture termed "Spice". JWH-018 is a CB1 and CB2 agonist with a higher affinity than Δ 9 -THC. In order to investigate the neurobiological substrates of JWH-018 actions, we studied by microdialysis in freely moving rats the effect of JWH-018 on extracellular dopamine (DA) levels in the nucleus accumbens (NAc) shell and core and in the medial prefrontal cortex (mPFC). JWH-018, at the dose of 0.25 mg/kg i.p., increased DA release in the NAc shell but not in the NAc core and mPFC. Lower (0.125 mg/kg) and higher doses (0.50 mg/kg) were ineffective. These effects were blocked by CB1 receptor antagonists (SR-141716A and AM 251) and were absent in mice lacking the CB1 receptor. Ex vivo whole cell patch clamp recordings from rat ventral tegmental area (VTA) DA neurons showed that JWH-018 decreases GABAA -mediated post-synaptic currents in a dose-dependent fashion suggesting that the stimulation of DA release observed in vivo might result from disinhibition of DA neurons. In addition, on the "tetrad" paradigm for screening cannabinoid-like effects (i.e., hypothermia, analgesia, catalepsy, hypomotility), JWH-018, at doses of 1 and 3 mg/kg i.p., produced CB1 receptor-dependent behavioural effects in rats. Finally, under appropriate experimental conditions, rats (20 μg/kg/inf i.v., FR3; nose-poking) and mice (30 μg/kg/inf i.v., FR1; lever-pressing) self-administer intravenously JWH-018. In conclusion, JWH-018 shares with the active ingredient of Marijuana, Δ 9 -THC, CB1-dependent reinforcing and DA stimulant actions. Highlights: JWH-018 is a full CB1 and CB2 agonist that has been frequently identified in Spice. JWH-018 increases NAc shell DA and decreases GABAA -mediated IPSC in VTA DA neurons. JWH-018 induces dose-dependent tetrad-like effects and IVSA in rats and mice. Spice effects suggest a greater prevalence of dependence and risk to health than MJ.